Obrazovni profil zaposlenih u službi za tretman u zatvorima u Srbiji - Petrović, Vera; Raspopović, Antonija (Specijalna edukacija i rehabilitacija, 2025)
Introduction. The treatment of convicted persons serving a prison sentence includes a series of activities that are carried out with the aim of their resocialization and reintegration into the social community. In addition to the many prerequisites that must be met regarding the conditions of prison life, for the treatment to be effective, it must be implemented by officers who possess adequate knowledge and skills for working with convicted persons. Objective. The objective of the research was to determine the characteristics of treatment officers related to their formal education, and to indicate the necessity of adequately selecting professional personnel who will work in penal institutions. Methods. The sample consisted of 43 treatment officers from penitentiaries in Sremska Mitrovica (39.5%), Požarevac (34.9%), and Niš (25.6%). There were 27 women (62.8%) and 16 men (37.2%) in the sample. Results. Research findings indicate that employees significantly more often had formal education to perform the duties of treatment officers (83.7%), and that within the employee structure, special educators (37.2%) were dominant. Significant differences in formal education were not detected in relation to whether the treatment officers were engaged in the department for personality testing or the department for the implementation of treatment, or according to the prison where they worked. Worthy of attention is the finding that only psychologists were present in all three prisons. Conclusion. Although the structure of employees in relation to formal education is favorable, it is important to invest additional efforts in order to have a diverse structure of treatment officers in Serbian prisons. In this way, each of them, from the domain of their expertise, and in accordance with the needs of convicted persons, could contribute to the fulfillment of the purpose of serving the prison sentence.
Keywords: prison; convicted persons; treatment service; treatment officers